"Keefektifan Media E-Comic Karakter Padepokan sebagai Upaya untuk Meningkatkan Pemahaman Pendidikan Karakter pada Siswa Sekolah Dasar - Lulut Solehhudin; Dewi Wulandari, Murfiah (Perspektif Ilmu Pendidikan, 2023)
Character education is an important thing that needs to be prepared from an early age to high school so that habits that are carried out do not only become a habit but also become a part of a person's character. Several problems developed in the field, especially the lack of education and the use of media in character education. This study seeks to evaluate the efficacy of Padepokan character e-comic media and ascertain the impact of character education on elementary school students' understanding. This study employed a quantitative approach with a quasi-experimental method and a nonequivalent control group design, in which the two groups were not selected at random. The object of research is Padepokan character comic media (X) and their ability to increase understanding of character education (Y). The population is 40 students, with a total of 20 students in each class. In its implementation, before being given treatment, both the experimental group and the control group were first given a pre-test as an initial test. Data collection techniques employing surveys, observation, and documentation To determine how effective the application of character-driven e-comic media is, descriptive analysis, straightforward regression analysis (t test), and a normalised gain test were used to analyse the data. The results showed that (1) there was a significant increase in understanding of character education in the average experimental class by using Padepokan character e-comic media (by 20.1%). (2) There was an increase in understanding of character education in the control class using conventional techniques of 14.3%; (3) there is a difference in the average gain score in the experimental class of 58.2%, while in the control class the average gain is 38.2%. This means that the use of Padepokan Character Comic Media in the experimental class is quite effective in increasing understanding of character education, while the use of conventional techniques is deemed ineffective in increasing understanding of character education.